Gaming and the virtual sublime : rhetoric, awe, fear, and death in contemporary video games - Spokes, Matthew (Emerald Publishing Limited, 2020)
Gaming and the Virtual Sublimeconsiders the 'virtual sublime' as a conceptual toolbox for understanding our affective engagement with contemporary interactive entertainment.